Mempersiapkan SDM Handal Dalam Menghadapi Smart Society 5.0 - Ahmad Syukri; Umi Rusilowati; Gatut Drajad Purwoko (Universitas Pamulang, 2022)
TECHNOLOGY is growing over time which is marked by the industrial revolution 1.0 to the industrial revolution 4.0. Along with the development of this technology resulted in changes in the pattern of social behavior of the community (society). This is evident from the beginning that every society's behavior was only centered on meeting the needs of the community without any influence from technology, but now every order of life and community needs will be centered on humans and based on technology. Currently the development of society is at the level of society 5.0. So what is meant by society 5.0? “Society 5.0 is defined as a human-centered society that balances economic progress with solving social problems through a system that deeply integrates virtual and physical space.”The concept of society 5.0 was initiated by the State of Japan and is considered as a complement to the concepts of the industrial revolution that already existed before. Where Japan has implemented Society 5.0 in January 2019. In society 5.0, it is hoped that the community can solve various economic and social challenges and problems by utilizing various innovations that were born in the era of the industrial revolution 4.0 such as the Internet on Things (internet for everything), Artificial Intelligence (artificial intelligence), Big Data (large amounts of data), and robots that can improve the quality of human life